GEOMORPHOLOGICAL ANALYSIS OF THE MEGHRI RIVER BASIN (REPUBLIC OF ARMENIA) FOR THE ASSESSMENT OF MUDFLOW HAZARD (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
Geomorphological features of the Meghri River basin (steep and near-vertical slopes; numerous straight and deep erosion furrows; deep drainage funnels in the upper reaches of rivers; intensive physical weathering of rocks on exposed slopes and accumulation of loose detrital material on them as a solid component for debris flows; predominance of the feathery pattern of the river network; steep thalwegs of all tributaries – falling within 119.0–194.5 m/km2, providing high energy to the water flow, etc.) determine its high debris flow hazard with a frequency of 1–3 years (sometimes up to 8 years). For the first time, morphometric coefficients (lemniscates, the development of the length of the dividing line, lengthening and elongation, and relative shape) of the basins of the largest tributaries of the Meghri River have been calculated and the effect of their features on debris flow hazard has been shown.
Keywords: basin shape; debris flow hazard; gradient of talweg; lemniscate